6x² + 2x - 20 = 0
3(2x² + x - 10) = 0
3[(2x² - 4x + 5x - 10)] = 0
3[2x(x - 2) + 5(x - 2)] = 0
3(2x + 5)(x - 2) = 0
3=0, 2x + 5 = 0, x - 2 = 0 (Note: 3=0 is false so disregard that equation)
x =
, x = 2
Answer: x = {
, 2}
1. Vertical shift, when k is outside of the parenthesis it indicates the translation up or down. Positive k is up and negative k is down.
2. Horizontal shift, when k is inside of the parenthesis it indicates the translation left or right. BE CAREFUL: positive k is left and negative k is right. Don’t get these mixed up
Answer:
D. pi
Step-by-step explanation: